Development of FinTech and BigTech companies and their expansion on the banking market - Folwarski, Mateusz (Rozwój spółek FinTech i BigTech i ich ekspansja na rynku bankowym, 2020)
The main research goal set in the article was to consider the reasons for the intensive development of the FinTech sector and the classification the BigTech sector − which may pose a greater threat to traditional financial institutions than the activities of FinTech companies. Surveys conducted among FinTech companies show that they have a positive impact on the financial market, leading, among others to the better adaptation of financial products and services to the needs of consumers. Companies from the FinTech sector increasingly cooperate with banks in the field of implementing financial innovations. Therefore, the financial products and services offered are relatively cheaper and delivered to consumers faster − especially during the period of progressing digitization of the financial market. FinTech companies note that consumers are attached to traditional financial institutions that have the status of public trust institutions and are characterized by a high level of reputation and stability
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 44-54
Keywords: FinTech; BigTech; traditional banking institutions; tradycyjne instytucje bankowe